DETECTION OF NUTRITIONAL RISK AT ADMISSION AND DISCHARGE OF ELDERLY PATIENTS ADMITTED TO A MILITARY HOSPITAL (Interdisciplinary Studies Journal, 2025)
Hospital admission is associated with several factors that can influence the nutritional status of elderly people. Malnutrition affects the patient's quality of life and general condition, leading to greater clinical complications. Therefore, it is extremely important to screen for nutritional risk during hospitalization. The research aimed to compare the prevalence of nutritional risk upon admission and discharge of elderly patients admitted to a military hospital. This is a quantitative study, with a cross-sectional design. The Nutritional Risk Screening 2002 (NRS-2002) tool was applied and anthropometric assessment of patients was carried out. 129 hospitalized elderly people were evaluated at admission and discharge. There was a nutritional risk prevalence of 49.6% at hospitalization, 45.1% upon admission and 55.2% upon discharge, with no statistical differences between admission and discharge. A higher nutritional risk was also found in males and older elderly people had a larger nutritional risk on admission, while young elderly people had a higher percentage at discharge. Patients with three or more comorbidities had a larger nutritional risk on admission. The study demonstrated great importance in assessing nutritional risk in hospitalized elderly people, so that assertive and targeted treatment strategies can be adopted, contributing to the improvement of their general condition.
Keywords: Nutritional Status; Elderly; Nutritional Risk